The readers of broken wheel recommend ebook - Bivald, Katarina (2016)
New York Times and USA Today Bestseller! Katarina Bivald's The Readers of Broken Wheel Recommend is a sweet, smart, and uplifting story about how books find us, change us, and connect us. Once you let a book into your life the most unexpected things can happen: Like the bestselling historical novel and Netflix film The Guernsey Literary and Potato Peel Pie Society, The Readers of Broken Wheel Recommend is a heartwarming reminder of why we love books. Broken Wheel, Iowa, has never seen anyone like Sara: Sara traveled all the way from Sweden just to meet her book-loving pen pal Amy, but when she arrives she finds Amy's funeral guests just leaving. The residents of Broken Wheel are happy to look after their bewildered visitor—there's not much else to do in a dying small town that's almost beyond repair. You certainly wouldn't open a bookstore. And definitely not with Sara the tourist in charge. You'd need a vacant storefront (Main Street is full of them), books (Amy's house is full of them), and...customers. The bookstore might be a little quirky. Then again, so is Sara. But Broken Wheel's own story might be funnier, more eccentric and surprising than she thought. If you liked big-hearted books like The Storied Life of A. J. Fikry or Eleanor Oliphant Is Completely Fine, you will love The Readers of Broken Wheel Recommend. Praise for The Readers of Broken Wheel Recommend: "The Readers of Broken Wheel Recommend is a warm and slyly funny look at small towns and romance..."— New York Journal of Books "A heartwarming tale about literature's power to transform."— People "What begins as an unlikely international friendship based on a mutual love of books becomes a sweet and soulful discovery of America. Quirky, unpredictable, funny, and fresh—a wonderful book."— Nickolas Butler, internationally bestselling author of Shotgun Lovesongs and Beneath the Bonfire International Bestseller Indie Regional Bestseller National Indie Bestseller #1 Indie Next Pick